Specification for bolts, double hexagonal heads, optional locking wire holes, unified threads, alloy steel, cadmium plated. Classification: Rm ≥ 1241 MPa (180 000 lbf/in2 ) at ambient temp | +190°C. (30th September 2019) - British Standards Institution,
No abstract available